2008
DOI: 10.1080/14764170802524403
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cellulite treatment with RF, IR light, mechanical massage and suction treating one buttock with the contralateral as a control

Abstract: Treatment sessions with the combined RF, IR light and mechanical massage and suction system were complication free, produced improvements in the overall cellulite appearance and skin condition, suggesting that further treatment sessions for maintenance could sustain patient satisfaction index (SI) and lead to lasting results. Based on the good results in the limited trial population, further studies with larger patient populations are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…Accordingly, several technologies such as laser diode [4], mesotherapy [5,6], cryotherapy, radiofrequency [7], lowfrequency and low-intensity nonthermal ultrasound (LOFU), high-intensity and high-frequency focused ultrasound (HIFU) [3,8], and even a combination of these techniques in the presence or absence of mechanical manipulation have been developed [9,10]. However, after being in use for a few years, adverse effects and/or unsatisfactory aesthetic outcomes have been reported for these techniques [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, several technologies such as laser diode [4], mesotherapy [5,6], cryotherapy, radiofrequency [7], lowfrequency and low-intensity nonthermal ultrasound (LOFU), high-intensity and high-frequency focused ultrasound (HIFU) [3,8], and even a combination of these techniques in the presence or absence of mechanical manipulation have been developed [9,10]. However, after being in use for a few years, adverse effects and/or unsatisfactory aesthetic outcomes have been reported for these techniques [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…High-and low-radiofrequency devices have been used. Combining radiofrequency with suction (750 mmHg negative pressure) in published randomized controlled trials (RCTs) showed no statistically significant improvement compared to monotherapy [6,7] . Hexsel et al [8] showed up to 78% patient satisfaction by using subcision, which improved skin dimpling by severing the septae8 that hold fat lobules resulting in skin dimpling.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, Romero et al [12] used the VelaSmooth device for the treatment of cellulite in 10 patients. Improvements in the overall appearance of cellulite and skin condition were achieved.…”
Section: Cellulitementioning
confidence: 99%